2001
DOI: 10.1097/00004872-200103000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of renal function in treated and untreated older patients with isolated systolic hypertension

Abstract: In older patients with isolated systolic hypertension, antihypertensive treatment starting with the dihydropyridine calcium-channel blocker, nitrendipine, did not decrease blood pressure at the expense of renal function and prevented the development of proteinuria, especially in diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(50 citation statements)
references
References 28 publications
0
44
1
5
Order By: Relevance
“…The discrepancy with the results from the SystChina trial, which also found a relationship between uric acid and complications, may be explained by the fact that other risk factors, such as elevated cholesterol, were less prominent in the Chinese patients (10). The reason that we found uric acid to be a less conspicuous indicator of cardiovascular risk could also be due to the limited increase in serum creatinine that we encountered in this study (25). Perhaps, a greater loss of renal function or a more pronounced fall in extracellular fluid volume (such as may occur during diuretic treatment) is necessary to unmask the role of uric acid as an independent marker of risk.…”
Section: Discussioncontrasting
confidence: 99%
“…The discrepancy with the results from the SystChina trial, which also found a relationship between uric acid and complications, may be explained by the fact that other risk factors, such as elevated cholesterol, were less prominent in the Chinese patients (10). The reason that we found uric acid to be a less conspicuous indicator of cardiovascular risk could also be due to the limited increase in serum creatinine that we encountered in this study (25). Perhaps, a greater loss of renal function or a more pronounced fall in extracellular fluid volume (such as may occur during diuretic treatment) is necessary to unmask the role of uric acid as an independent marker of risk.…”
Section: Discussioncontrasting
confidence: 99%
“…erates renal progression in hypertensive subjects (21,22,(147)(148)(149)(150)(151)(152)(153)(154)(155). The usage of diuretics in the EWPHE (22,153), Syst-Eur (149), SHEP (150), INSIGHT (151), and ALLHAT (152) studies were all statistically associated with a greater decline in renal function compared with the other treatment groups.…”
Section: Specific Characteristics That Favor An Increased Risk For Rementioning
confidence: 99%
“…In the patients assigned randomly to receive active treatment, the incidence of mild renal dysfunction decreased by 64%, and that of proteinuria by 33%. [86] 250…”
Section: Effects On the Progression Of Human Renal Diseasementioning
confidence: 99%